Kehandalan pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap - Sani, Zul Fadli; Imallah, Rosiana Nur; Masitoh, Rohayati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Patient satisfaction in hospitals can be achieved through the quality of nursing services provided, one of which is nurse reliability. Nurses with reliability are those who meet patient expectations, such as keeping promises, resolving problems effectively, providing satisfaction, and demonstrating a trustworthy attitude. Purpose: To determine the relationship between nursing service reliability and patient satisfaction in inpatient wards. Method: This quantitative study used a descriptive correlation design with a cross-sectional approach. The sampling technique used purposive sampling, with a sample size of 97 respondents. The research instrument used a questionnaire. Data analysis used the Kendall Tau test. Results: The reliability of nursing services was categorized as good by 81 respondents (83.5%), while patient satisfaction was categorized as satisfied by 78 respondents (80.4%). The data analysis yielded a value of 0.015 <0.05. Conclusion: There is a relationship between nursing service reliability and patient satisfaction in inpatient wards.   Keywords: Nursing Services; Patient Satisfaction; Reliability.   Pendahuluan: Kepuasan pasien di rumah sakit dapat tercipta dari kualitas pelayanan keperawatan yang diberikan salah satunya adalah kehandalan perawat. Perawat yang memiliki kehandalan yaitu kemampuan untuk memenuhi harapan pasien seperti menepati janji, menyelesaikan permasalahan dengan baik, memberikan kepuasan, serta menunjukkan sikap yang dapat dipercaya. Tujuan: Untuk mengetahui hubungan kehandalan pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap. Metode: Penelitian kuantitatif dengan rancangan deskriptif korelasi dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan Purposive Sampling, dengan jumlah sampel 97 responden. Instrumen penelitian menggunakan kuesioner. Analisis data menggunakan Uji Kendall Tau. Hasil: Kehandalan pelayanan keperawatan mayoritas berada pada kategori baik sebanyak 81 responden (83,5%) dengan kepuasan pasien berada pada kategori puas sebanyak 78 responden (80,4%). Hasil analisis data diperoleh nilai 0.015<0.05. Simpulan: Terdapat hubungan antara kehandalan pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap.   Kata Kunci : Kehandalan; Pelayanan Keperawatan; Kepuasan Pasien